(untitled) (Palíndromo, 2016)
In this essay I propose the articula- tion of the problem of the thesis writing from the texts selected in Research Se- minar I discipline. The passion for resear- ch is a leap into self-knowledge.The fate- ful question ‘who are we?’ becomes both unsettling and exciting when we unders- tand that there is not an answer that sa- tisfies such a sentence. Whatever such responses are always multiple, permea- ble, fluid and ephemeral; transitive eter- nal pathways between the absolute and the peculiar. Then explained the search: conscious human action in an attempt to share a subjective perspective that dialo- gue in the collective and, so being, can come to expand the various modes of existence and ideas about the world and ourselves.